Recommending HPV vaccination at age 9 to reduce health disparities: Communication challenges and opportunities - Tamera Coyne-Beasley; Rebecca R. Ortiz (Taylor & Francis Group, 2023)
The HPV vaccine is approved for children as young as age nine and recommended by the Centers for Disease Control and Prevention's Advisory Committee on Immunization Practices routinely for ages 11-12. However, many U.S. adolescents do not complete the vaccine series until middle to late adolescence, if at all, leaving them vulnerable to future HPV infection and attributable cancers. Health disparities exist for both vaccination coverage and most HPV-associated cancers. A strategy for improving vaccination rates for all populations and reducing disparate gaps in protection and health disparities from HPV-associated cancers is to shift the routine recommendation to an earlier age, that is, to start the vaccine series at age nine instead of ages 11-12. Challenges, opportunities, and suggestions for communicating this recommendation are outlined alongside considerations of social determinants of health.